Life Satisfaction Among E-Sport Athletes: A Quantitative Descriptive Study - Utami Femina Sari Budiman, Angel; Elizabeth Zega, Fonny; Rizla Humairo, Alifia (Lafadz Jaya Publisher, 2024)
E-sport, a rapidly growing competitive field, offers promising career opportunities for many individuals. However, the intense training regimens, isolation from broader social interactions, and performance pressures can significantly impact the life satisfaction of E-Sport athletes. This study aims to describe the life satisfaction levels among E-Sport athletes. A quantitative descriptive approach was employed using non-probability sampling with a purposive sampling technique. The sample consisted of 100 E-Sport athletes. The Satisfaction with Life Scale (SWLS) based on Diener's (1984) theory, comprising 26 valid items with a reliability coefficient of 0.933, was utilized as the measurement tool. Results indicate that 57% of athletes reported high life satisfaction. Specifically, 80.6% had high satisfaction with future life, whereas 60% had low satisfaction with their past life. Early adult male E-Sport athletes with incomes between 5,000,000 - 7,000,000 IDR and greater than 10,000,000 IDR, training for 16-24 hours, and participating in over 10 tournaments had higher life satisfaction. Conversely, athletes earning 3,000,000 - 5,000,000 IDR, training for 10-15 hours, and participating in fewer than eight tournaments reported lower life satisfaction.